2002
DOI: 10.1128/jcm.40.9.3135-3139.2002
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of Candida albicans with C. dubliniensis in Human Immunodeficiency Virus-Infected Patients with Oropharyngeal Candidiasis Treated with Fluconazole

Abstract: Candida dubliniensis is an opportunistic yeast that has been increasingly implicated in oropharyngeal candidiasis (OPC) in human immunodeficiency virus (HIV)-infected patients but may be underreported due to its similarity with Candida albicans. Although most C. dubliniensis isolates are susceptible to fluconazole, the inducibility of azole resistance in vitro has been reported. Thus, the use of fluconazole prophylaxis in the treatment of these patients may have contributed to the increasing rates of isolation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
69
3
10

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(84 citation statements)
references
References 30 publications
2
69
3
10
Order By: Relevance
“…Resistance to antifungal agents can be defined as the persistence or progression of infection after application of antimicrobial treatment [16,17]. Some studies have observed the emergence of resistant microorganisms during long-term or prophylactic treatment [18,19]. Intrinsic or primary resistance occurs when a microorganism has low susceptibility to a medication, before its exposure to the agent.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance to antifungal agents can be defined as the persistence or progression of infection after application of antimicrobial treatment [16,17]. Some studies have observed the emergence of resistant microorganisms during long-term or prophylactic treatment [18,19]. Intrinsic or primary resistance occurs when a microorganism has low susceptibility to a medication, before its exposure to the agent.…”
Section: Introductionmentioning
confidence: 99%
“…dubliniensis (19). It did not occur in the replacement of both species in this study because the subjects were healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…TRB+VRZ resulted on 53.33% of indifference and synergy decreased The increased use of antifungal agents may have contributed to the development of highly resistant microorganisms or those which are more prone to develop resistance to drugs such fluconazole. 11 Although most C. dubliniensis clinical isolates are susceptible to azole derivatives, resistant strains have been recovered from oral cavities of human immunodeficiency virus (HIV)-infected patients with oropharyngeal candidiasis and prior exposure to fluconazole. 8,12 Thus, combining antifungal agents has been suggested as an alternative strategy, and the use of terbinafine in combination with azoles has been suggested as a potential therapeutic option.…”
Section: Brief Communicationmentioning
confidence: 99%